Pengaruh Persepsi Harga dan Kualitas Produk Terhadap Keputusan Pembelian Rokok Elektrik di Toko Dzikra Vape Sengkang - Andi Sumangelipu; Muzakkir; Besse Nurul Hikmah (Precise Journal of Economic, 2024)
The history of vaping in Indonesia reflects a significant shift in tobacco consumption patterns, particularly among young people. Since the introduction of electronic cigarettes (e-cigarettes) around 2014, their popularity has surged, with usage increasing significantly in recent years. According to data from the Indonesian E-Cigarette Association (AREI), the number of e-cigarette users in Indonesia is increasing rapidly, reaching over 4 million people in 2022. One factor influencing purchasing decisions for these products is perceptions of price and product quality. Therefore, this study aims to analyze how perceptions of price and product quality influence purchasing decisions in the e-cigarette market, particularly in Sengkang City. The study used quantitative methods analyzed using multiple linear regression and partial and simultaneous testing to determine the relationship between each variable. The results of this study indicate that the variables of price perception and product quality have a strong positive relationship with purchasing decisions.